HUBUNGAN ANTARA PARAMETER BAKTERIOLOGI DENGAN AWITAN DAN EPISODE ERITEMA NODOSUM LEPROSUM PADA PENDERITA LEPRA MULTIBASILER - , EKA LISTYRINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Leprosy may cause a serious health problem because of its disability and reaction that becomes chronic. One of the reaction is ENL which is correlated with higher BI and MB type of leprosy. BI and MI are easy to do for bacteriological parameter. There are some studies supporting the correlation between ENL with BI, but the correlation between bacteriological parameter with onset and episode of ENL hasnât been studied yet. Objective : To evaluate the correlation of bacteriological parameter to the onset and episode of ENL BL/LL leprosy patients. Methods : Observational study with a retrospective cohort design. Results : A number of 137 (44,3%) patients were included in this study was taken from 309 patients, 92 (67,2%) male and 45 (32,3%) female. 99 (72,3%) BL/LL patients had ENL, 8% patients had acute episodes, 28% patients multiple acute, and 63% patients chronic ones. The mean initial BI was 4,20Â±0,85 and initial MI was 41,53Â±23,68%. Initial bacteriological parameter has a significant correlation with ENL onset (p<0,05), but initial parameter has no correlation with ENL episodes. This study showed that there was correlation between onset of ENL and initial BI and initial MI value. The higher initial BI the faster ENL occur while higher initial MI would slow done the onset of ENL. Nevertheless initial BI and MI value did not have any significant correlation with episode of ENL. Conclusion : There is significant correlation between initial bacteriological parameter with ENL onset, but there is no correlation with ENL episodes.